Eksistensi Pemikiran Pendidikan Islam Fazlur Rahman di Era Digital - Suwahyu, Irwansyah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This research examines the existence of Islamic education thought of one of the reformers in the 20th century, namely Fazlur Rahman. This research is a library research in which the subject of Fazlur Rahman's educational thought becomes the study in this research. Fazlur Rahman's thoughts in Islamic education are then connected with how the development of today's digital age. The result of this research is that Fazlur Rahman's thoughts have provided high standards on how the implementation of ideal education in Islamic educational institutions should be. This begins with formulating the right goals in accordance with the achievement of good physical and spiritual needs or a balanced world and hereafter. Then the education system is integrated between religious and general sciences. As well as the scientific development of students in accordance with their needs and related to critical, historical and holistic or comprehensive material. Apart from that, teachers are also no less important in taking a role in advancing education itself. Teachers are expected to always be able to answer the challenges and developments of the times in order to present knowledge with the latest media and methods. Finally, in infrastructure or all facilities that support the implementation of the educational process properly, it is very necessary to fulfill and improve the facilities in the process of sustainability of Islamic education. In this sophisticated era, the existence of Fazlur Rahman's thought is maintained. This is very strong if it is associated with the points of thought that are always progressive to see the developments that occurred at that time in the Western world and the decline occurred in the Islamic world. So Muslims should also pay attention to the times that occur with the presence of various kinds of progress in various matters and this must be responded positively by Muslims, especially in the field of education.Keyword: Islamic Education Thought; Fazlur Rahman; Digital Era.